Construction of a high-sensitivity Cherenkov luminescence endoscopy system for the detection of gastrointestinal cancers - Ze Yang; Tian-Tian Pang; Zhuo-Jun Wu; Tian-Yu Yan; Jing-Min Yu; Xin-Yu Wang; Dan Liu; Xiao-Jian Lu; Xiao-Yu Kang; Gui-Yu Li; Cheng Bai; Xiao-Juan Xi; et al. (EJNMMI Research)
Abstract Background The diagnostic yield of conventional gastrointestinal (GI) endoscopy for early cancers is low because it is mainly based on morphological changes of tumors. Molecular functional changes in tumors precede morphological changes. Cherenkov luminescence endoscopy (CLE) system can perform molecular imaging of GI cancers, achieving early diagnosis of cancers. However, previous CLE systems had only been able to detect Cherenkov luminescence (CL) from about one μCi nuclide at a minimum (in vivo), but the nuclide probe absorbed by the tumor of a patient was often much less than one μCi at a routinely administered dose. This study aims to construct a clinically usable high-sensitivity CLE for molecular imaging of GI cancers. Results The minimum resolvable radioactivity of the CLE reached 0.020 μCi within 300 s (in vivo), with a sensitivity at the nanocurie for the first time. The detection sensitivity of the CLE increased by up to nearly twenty-two times over the previous system. In tumor-bearing nude mice, CLE could effectively identify all tumors with 100% concordance with both histopathology and PET/CT, and the CL signals of tumors were much stronger than those of the surrounding normal tissues (P < 0.05). The quality of CLE imaging at 60 s was comparable to that at 300 s (signal-to-background ratio, 2.70 ± 0.48 versus 2.98 ± 0.69, P = 0.56). Conclusions We constructed a high-sensitivity CLE that could detect radionuclides at the nanocurie radioactivity. The CLE could detect cancers accurately through rapid molecular imaging and had the potential for early diagnosis of GI cancers in clinical practice.